2020
DOI: 10.33448/rsd-v9i11.9452
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium in artisanal ripening cheese: technological and safety aspects

Abstract: The aims of this work were to identify and characterize for some important technological properties of the E. faecium throughout the ripening process of cheese. The study involved evaluating the technological potential of six isolates of E. faecium (EFM55, EFM67, EFM9A, EFM16A, EFM19A and EFM44) from artisanal cheeses as their probiotic characteristics and technological perspective. Concerning the antimicrobial sensibility, 71% of the E. faecium tested were sensitive to all antimicrobials. No other medicine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Concerning the pili gene clusters PGC-3 and PGC-4, none of the strains showed complete identity profiles for the entire array of genes forming the PGCs. The lack of genetic markers for virulence, incomplete set of PGCs [1–4], together with the susceptible ampicillin genotype of E. lactis and clade B, support the safety of this taxonomic unit and the clear separation from virulent and AM resistant isolates (Clade A2 and A1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the pili gene clusters PGC-3 and PGC-4, none of the strains showed complete identity profiles for the entire array of genes forming the PGCs. The lack of genetic markers for virulence, incomplete set of PGCs [1–4], together with the susceptible ampicillin genotype of E. lactis and clade B, support the safety of this taxonomic unit and the clear separation from virulent and AM resistant isolates (Clade A2 and A1).…”
Section: Resultsmentioning
confidence: 99%
“…It is found in a large number of foods, mainly fermented products of animal origin like cheeses and dry sausages [1], where they are part of the natural ripening processes or added as starter cultures. Some strains of this species have been recognized also as probiotics conferring benefits to their hosts [2, 3]. However, in the past three decades, E.…”
Section: Introductionmentioning
confidence: 99%
“…isolates from Kashar cheese lowered it to 4.08 for 24 h [106]. According to results reported by de Paula et al [107], better acidification values can be achieved by prolonging cultivation time. A few authors reported that E. faecalis strains reduce milk pH faster than E. faecium and E. durans strains [22,108].…”
Section: Acidification Activitymentioning
confidence: 99%